Association of childhood vaccination with pediatric lichen planus: A systematic review. (6th December 2021) - Bansal, Deepty; Kamboj, Mala; Anand, Rahul; Pandiar, Deepak; Narwal, Anjali; Sivakumar, N.; Devi, Anju
Abstract: Lichen planus (LP) is a chronic T‐cell‐mediated mucocutaneous inflammatory disease, largely recognized in adults. It is uncommon in children, and the literature present still lacks comprehensive understanding mainly due to underreporting of such cases. LP shows atypical clinical features, when seen in children, mainly affecting the flexor aspect of the wrists, legs, and the oral and genital mucosae. It is largely considered an autoimmune response of the body with various etiologic factors. Its association with vaccination is still an interesting field for research. The focus of the present systematic review was to discover the link of vaccine in the pathogenesis of juvenile LP. An electronic search was carried out using MEDLINE by PubMed, Google Scholar, and Web of Science databases. Articles that reported LP in children with prior records for vaccination were selected for the present systematic review. Twenty‐three published articles in the English language were included for the quantitative and qualitative syntheses. The demographic data, specific vaccine history, and clinical details of the lesions were recorded. The existing evidence supports that vaccines could play an important role in etiopathogenesis of pediatric LP.